Desjudicialização dos conflitos: novo paradigma para uma educação jurídica voltada à prática da atividade advocatícia negocial - Brandão, Fernanda Holanda de Vasconcelos (2014)
The practical experience of courses provided by Law Schools in Brazil shows that the legal education is not following the contemporary social transformations. On the other hand, the society is increasingly seeking for a more efficient, non-bureaucratical and speedier access to justice. However, this access is not being possible through traditional means of conflict resolution, what means lawsuits. Actually, the Judiciary seems inadequate in order to attend a constantly growing number of procedures and law professionals do not have awareness that we must privilege the pacification culture over the litigation culture. Therefore, due to so many crisis, either in Judiciary, in State, in the university legal education, it is necessary to find ways to provide practical and real effectiveness to make the access to justice as a citizen fundamental right, consequently, contributing to promote social, human and economic development in the democratic rule-of-law State. To achieve this objective, it must exist a join effort of society, legislators, legal scholars and students, in order to change the paradigm of a dogmatic and archaic legal education, which has its foundations in the history of a centralized and absolute Law, guided by utilization and application of what the laws dictate. This overpassed educational method, nowadays countered by several jurists, always withdrew the critical and interpretational power of the people, as it is evident in studies of the jurist theoretical common sense. Considering those aspects, this work aims to disseminate the phenomenon of extrajudicial conflict resolution as a new paradigm to be adopted for a legal education dedicated to alternative dispute resolution founded in negotiation techniques and game theory.